(untitled) (Sustainability in Debate, 2017)
Dolphin watching touristic activities can contribute both to the conservation of dolphins and to the development of the local economy. As a part of the management plan of the Coastal Wildlife Reserve of Tibau do Sul (Refauts), the present study aimed to evaluate Guiana dolphin watching activities. During the expeditions to the study area, interviews were conducted among boat drivers. The research also included censuses and inspections of licensed tourism boats, as well as a record of the dolphin watching touristic flow. Within a sample of 16 days of observation, a total of 11 licensed tourism boats operating in Refauts was registered, along with 368 observation tours and a 4,717 tourists. Results showed that - in 30% of the registries - boat drivers did not comply with the legal determinations for the Refauts area, which limit the number of boats operating in the bays. Results also show that Guiana dolphin watching activities in Refauts have played an important role in the development of the local economy, but an action plan is still necessary in order to ensure the conservation of Guiana dolphins in Refauts.